(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study examines the linguistic beauty and moral values in Imam Syafi‘i’s poetry regarding the ethics of seeking knowledge. As both a profound jurist and a literary figure, Imam Syafi‘i integrated philosophical depth into beautiful and communicative linguistic structures. This qualitative research employs content analysis and a hermeneutic approach toward the texts in Diwan al-Imam al-Shafi’i. The results reveal that Imam Syafi‘i utilizes a powerful pedagogical-realism style, using "bitter" (murr) diction to cultivate mental resilience in students. The aesthetic beauty of the poetry is manifested through metaphors, hyperboles, and antitheses, such as the "funeral prayer" analogy for youth who neglect education. Substantively, these verses convey character education values emphasizing respect for teachers, the urgency of time, and the integration of knowledge and piety as pillars of human existence. This analysis concludes that the linguistic aesthetics serve as a rhetorical instrument to strengthen moral messages, maintaining their relevance for modern character development.